2016
DOI: 10.1037/xlm0000209
|View full text |Cite
|
Sign up to set email alerts
|

Incidental biasing of attention from visual long-term memory.

Abstract: Holding recently experienced information in mind can help us achieve our current goals. However, such immediate and direct forms of guidance from working memory are less helpful over extended delays or when other related information in long-term memory is useful for reaching these goals. Here we show that information that was encoded in the past but is no longer present or relevant to the task also guides attention. We examined this by associating multiple unique features with novel shapes in visual long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…These results have demonstrated that simply holding an item in WM was not sufficient for control (Hutchinson & Turk-Browne, 2012;Woodman & Chun, 2006). This proposal was supported by experimental investigations in which the content of LTM has been shown to optimize perceptual sensitivity (Stokes, Atherton, Patai, & Nobre, 2012) and induce attentional capture (Fan & Turk-Browne, 2016;Olivers, 2011). Nevertheless, the interaction between the predictive information in LTM and distractor suppression remained less explored.…”
Section: Introductionmentioning
confidence: 74%
“…These results have demonstrated that simply holding an item in WM was not sufficient for control (Hutchinson & Turk-Browne, 2012;Woodman & Chun, 2006). This proposal was supported by experimental investigations in which the content of LTM has been shown to optimize perceptual sensitivity (Stokes, Atherton, Patai, & Nobre, 2012) and induce attentional capture (Fan & Turk-Browne, 2016;Olivers, 2011). Nevertheless, the interaction between the predictive information in LTM and distractor suppression remained less explored.…”
Section: Introductionmentioning
confidence: 74%
“…On the other hand, distractors with associative links to the target disrupt the visual search by capturing attention (Moores et al., 2003). Furthermore, newly learned associations continue to affect performance on subsequent tasks, even when completely irrelevant (Fan and Turk-Browne, 2016).…”
Section: Main Textmentioning
confidence: 99%
“…People are slower to respond on a visual search task when an item matching an item held in working memory is presented as a distractor (attentional capture). A broad range of mental states and processes can bias our attention, including visual working memory, verbal working memory, long‐term memory, associative knowledge, implicit memory, and reward . Studies have found converging evidence for attentional capture when the working memory load is held to a single item (although see Refs.…”
Section: Introductionmentioning
confidence: 99%